Legacy of Datuk Seri Mohd. Shafie Apdal (DSSA) in Semporna’s Parliament in GE-14 - Nordin Sakke; Md Saffie Abd. Rahim; Ramli Dollah; Amrullah Maraining; Wan Shawaluddin Wan Hassan; Fadilah Sarbi (2018)
Semporna is a maritime district located on the east coast of Sabah. In the last GE-14, most of political analysts were concentrating on Semporna because of Sabah’s political reformation begun in this area when the DSSA resigned from UMNO and formed Warisan Party. Many claimed that the action of DSSA as digging its own grave and will end his political life that has been built since 1995. But the results of the GE-14 said the opposite in fact he has been successfully appointed as the Chief Minister of Sabah. So, this paper tries to study the history of DSSA’s political involvement that has led to its legacy includes forcing himself to face for the legacy of his mentor,Tun Sakaran. To understand this issue, the election results starting from GE-9 were analyzed along with an analysis of the content of on-line media reports. Through this analysis, it was found that DSSA was an important character in Semporna’s politics. This is indicated by the number of popular votes in a contested general election remained above 70 per cent. Although the people of Semporna are synonymous with USNO and UMNO but the shifting of DSSA to Warisan Party, does not affect the people’s support for him. This is evidenced by the number of majority votes obtained by the GE-13 and the GE-14 is amounting 20,000 votes. Furthermore, the DSSA party was able to maintain a popular vote of 74.2 percent in DUN Senallang and 75.4 percent in the DUN Bugaya when facing the Tun Sakaran legacy.